Recursion Theory and Computational Complexity - Lolli, G.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
S. Homer: Admissible recursion theory.- B.E. Jacobs: Computational complexity and recursion theory.- D. Normann: A survey of set recursion.- G.E. Sacks: Priority arguments in Higgler recursion.- R.I. Soare: Construction in the recursively enumerable degrees.- W. Maass: Recursively invariant recursion theory.
S. Homer: Admissible recursion theory -- B.E. Jacobs: Computational complexity and recursion theory -- D. Normann: A survey of set recursion -- G.E. Sacks: Priority arguments in Higgler recursion -- R.I. Soare: Construction in the recursively enumerable degrees -- W. Maass: Recursively invariant recursion theory.
Keywords: Mathematics; Logic, Symbolic and mathematical; Mathematics; Mathematical Logic and Foundations